2014
DOI: 10.3109/03639045.2014.948452
|View full text |Cite
|
Sign up to set email alerts
|

Process and formulation variables of pregabalin microspheres prepared by w/o/o double emulsion solvent diffusion method and their clinical application by animal modeling studies

Abstract: Pregabalin is an anticonvulsant drug used for neuropathic pain and as an adjunct therapy for partial seizures with or without secondary generalization in adults. In conventional therapy recommended dose for pregabalin is 75 mg twice daily or 50 mg three times a day, with maximum dosage of 600 mg/d. To achieve maximum therapeutic effect with a low risk of adverse effects and to reduce often drug dosing, modified release preparations; such as microspheres might be helpful. However, most of the microencapsulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…According to this, it was observed that increasing concentration of span 80 from 1% to 4% caused the decrease of particles size from 558.3 ± 31.39 to 397 ± 22.73 nm. Similarly, Jose et al [33] and Aydogan et al [34] have reported that higher span 80 concentration caused the smaller particle size when they prepared diltiazem-loaded microspheres and pregabalin-loaded microspheres, respectively. Relatedly, Huang et al [35] reported that this surfactant agent (span 80) diminished particle size by reducing surface tension between liquid paraffin and organic phase in 5-fluorouracil-loaded microparticles.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…According to this, it was observed that increasing concentration of span 80 from 1% to 4% caused the decrease of particles size from 558.3 ± 31.39 to 397 ± 22.73 nm. Similarly, Jose et al [33] and Aydogan et al [34] have reported that higher span 80 concentration caused the smaller particle size when they prepared diltiazem-loaded microspheres and pregabalin-loaded microspheres, respectively. Relatedly, Huang et al [35] reported that this surfactant agent (span 80) diminished particle size by reducing surface tension between liquid paraffin and organic phase in 5-fluorouracil-loaded microparticles.…”
Section: Resultsmentioning
confidence: 86%
“…In fact, span 80 tends to reduce surface tension between the two phases, thereby preventing coalescence of particles by forming a thin layer around the droplets while stabilizing the emulsion. When the amount of span 80 in formulation falls below a certain concentration, droplets tend to aggregate because of insufficiency of surface tension reducing effect of surfactant agent and thus particle size is increased [33][34][35][36]. Figure 2 shows SEM microphotograph of AMO-loaded nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectra of Ketoprofen, Eudragit EPO, Ketoprofen:Eudragit EPO physical mixture (drug:polymer ratio; 1:2) and Ketoprofen:Eudragit EPO taste-masked granules (drug:polymer ratio; 1:2) were obtained by KBr disc method 9 (1:100 physical mixture; Shimadzu 8400S) in the range of 400-500 cm À1 .…”
Section: Fourier Transform Infrared Spectroscopy Analysismentioning
confidence: 99%
“…Tween 80 being a surfactant played an important role in determining the size of microsphere and percentage yield of the microsphere which in turn controls the drug release. 23 Different amounts of ethyl cellulose and surfactant were used in a 3^2 factorial design to identity a combination that would give a programmed release of 8 hours, small particle size and high percentage yield (Table 1). Multiple linear regression analysis was performed to equate the multiple factors with each response and mathematical models were generated.…”
Section: Preparation and Evaluation Of Microspheresmentioning
confidence: 99%